Analysis of the Active Metabolites of Ethanol and Ethyl Acetate Extract of Justicia carnea (African Journal of Biomedical Research, 2023)
Justicia carnea is a medicinal plant that has been used traditionally as a blood tonic and has other diverse therapeutic benefits for humans since time immemorial in Nigeria. This study is aimed at the analysis of the active metabolites in ethanol and ethyl acetate extracts of Justicia carnea. A powdered sample was extracted using absolute ethanol and ethyl acetate and concentrated with a rotary evaporator. Active metabolites were identified via column chromatography (CC) and gas chromatography-mass spectrometry (GC-MS). Ethanol was a more effective solvent for the extraction as most of the phytochemicals were identified in this extract. There was also extraction of other classes of active metabolites with a mixed solvent of petroleum ether, diethyl ether, and ethanol from crude ethyl acetate extract. Results from this study identified some active metabolites that possess a lot of therapeutic properties such as anti-microbial, anti-inflammatory, anti-diabetic, immune modulatory, and antimalarial activities that are of immense benefit to man.